The poverty industry: the exploitation of America's most vulnerable citizens - Hatcher, Daniel L. (Families, law, and society series, 2016)
How the poverty industry is siphoning aid from the vulnerable -- Agency purpose versus agency self-interest: conflict in serving the vulnerable -- Poverty's iron triangle -- Mining foster children for revenue -- Medicaid money laundering -- Cost recovery: poverty industry taking child support from children and families -- The expanding web of the poverty industry -- Reeling in the poverty industry: restoring agency purpose, and restoring fiscal -- Integrity to the safety net